Traumatic Brain Injury and Its Effect on Coagulopathy - McCully, Sean P.; Schreiber, Martin A. (Seminars in Thrombosis and Hemostasis, 2013)
Polytraumatic injury results in tissue factor (TF) release from damaged cells. The acute coagulopathy of trauma (ACT) occurs early and results from significant tissue injury and tissue hypoperfusion. ACT is augmented by therapies resulting in acidemia, hypothermia, and hemodilution contributing to trauma-induced coagulopathy. Coagulopathy associated with traumatic brain injury (TBI) results from the interplay of numerous variables. Because of the high concentration of TF in brain tissue, TBI has been believed to be associated with a greater degree of coagulopathy compared with injury in other body systems. TBI has also recently been shown to cause platelet dysfunction. Platelet receptor inhibition prevents cellular initiation and amplification of the clotting cascade, limiting thrombin incorporation, and stabilization of clot to stop hemorrhage. Therefore, head injury in the presence of polytrauma does appear to augment ACT and warrants close monitoring and appropriate intervention.
Keywords: trauma; hemostasis; coagulopathy; traumatic brain injury